Multi-Dimensional Self-Assembly of a Dual-Responsive ABC Miktoarm Star Terpolymer - Xu, Fugui; Wu, Dongdong; Huang, Yinjuan; Wei, Hao; Gao, Yong; Feng, Xinliang; Yan, Deyue; Mai, Yiyong (ACS Macro Letters, 2017)
This letter reports the first 2D self-assembly of ABC miktoarm star terpolymers based on dual-responsive polycaprolactone-arm-poly(N-isopropylacrylamide)-arm-poly(2-dimethylaminoethyl methacrylate) (μ-CID), which self-assembled into multilayer nanosheets comprising polycaprolactone single crystals in tetrahydrofuran (THF)/methanol mixed solvents. Interestingly, the nanosheets showed pH-responsive morphological transitions in aqueous solutions, yielding multidimensional assemblies, including 2D hexagonal aggregates, patchy nanofibrils, and patchy vesicles, at different pH values. The nanosheets also exhibited thermoresponsive transition to spherical patchy micelles at a temperature above the lower critical solution temperature (LCST) of the poly(N-isopropylacrylamide) block. This study offers a novel system for fundamental study on the self-assembly of miktoarm star terpolymers.
CRIS-Team Scopus Importer:2023-03-20